Review Artkel Efek Sinergis Ekstrak Nabati terhadap Pengendalian Bakteri Patogen pada Produk Pertanian dan Kesehatan - Rezky Maulidiya; Ardi Mustakim (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Vegetable ingredients are natural sources of active compounds that have the potential to be used as control agents for pathogenic microorganisms in various fields, including health and agriculture. This study aims to evaluate the synergistic effect between aloe vera (Aloe vera L.) and bandotan (Ageratum conyzoides L.) extracts on inhibiting the growth of pathogenic bacteria in different media. Aloe vera extract is obtained using the infundation method, while bandotan extract is obtained using the maceration technique. The concentrations tested were 30%, 45%, and 60% for each extract, as well as a combination of both. Testing was carried out on two main applications: as an antiseptic hand sanitizer by testing germ colonies using Plate Count Agar (PCA), and as a bacteria control Erwinia carotovora, the cause of carrot tuber rot, using the Path Ways Analysis test. The results showed that the combination of aloe vera and bandotan extracts had more significant inhibitory effectiveness than single extracts in both applications. A combination concentration of 60% gave the best results with a reduction in bacterial colonies of up to 90%. The mechanism of action of active compounds such as flavonoids, phenolics and saponins in this vegetable extract plays an important role in damaging bacterial cell membranes and inhibiting the metabolism of microorganisms. This research confirms the potential of using local plant materials as an environmentally friendly and economical solution for controlling pathogenic bacteria in the health and agricultural sectors.